2019
DOI: 10.3390/antiox8080269
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet and microRNAs Linked to Antioxidant Biochemical Homeostasis

Abstract: Recently, we demonstrated the capability of the ketogenic diet (KD) to influence the microRNA (miR) expression profile. Here, we report that KD is able to normalize miR expression in obese subjects when compared with lean subjects. By applying two different bioinformatics tools, we found that, amongst the miRs returning to comparable levels in lean subjects, four of them are linked to antioxidant biochemical pathways specifically, and the others are linked to both antioxidant and anti-inflammatory biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…Indeed, even if orally introduced, bioactive dietary factors induce miRNA synthesis, these are packaged into exosomes and released into the bloodstream to act systemically (51). Dietary factors are emerging as anti-inflammatory miRNA promoters able to regulate metabolic functions, inflammation, and oxidation systemically (52)(53)(54)(55). Furthermore, herb extracts may combine antiviral, anti-inflammatory, and antioxidant activity, and tissue-repair properties (56,57) (Figure 1).…”
Section: Can Nutritionally Derived Products Help To Contain/alleviatementioning
confidence: 99%
“…Indeed, even if orally introduced, bioactive dietary factors induce miRNA synthesis, these are packaged into exosomes and released into the bloodstream to act systemically (51). Dietary factors are emerging as anti-inflammatory miRNA promoters able to regulate metabolic functions, inflammation, and oxidation systemically (52)(53)(54)(55). Furthermore, herb extracts may combine antiviral, anti-inflammatory, and antioxidant activity, and tissue-repair properties (56,57) (Figure 1).…”
Section: Can Nutritionally Derived Products Help To Contain/alleviatementioning
confidence: 99%
“…Bioactive dietary components could have the ability to change miRNA expression, thereby modulating important pathways involved in metabolism [ 20 , 21 , 39 , 40 ]. MiRNAs are involved in the expression of a widespread range of proteins and their consequent effect on metabolic functions and the maintenance of oxidative stress [ 41 ]. Therefore, it seems reasonable to assume that some bioactive compounds present in different foods may modulate the development and progression of certain diseases through miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, naringenin biochemical activity inhibits migration and invasion, as well as tumor growth, through the regulation of the microRNA-3619-5p, which belong to a regulating axis with circular RNA FOXM1 and sperm-associated antigen 5 [ 39 ]. Lastly, Curti et al recently demonstrate that naringenin is able to affect the miR-17-3p involved in the control of antioxidant endogenous system [ 40 ]. Using a Caco cell, a well characterized in vitro model which mimics the intestinal barrier, it is demonstrated that single enantiomers of naringenin R and S have similar activity on this miR, while their equimolar racemic mixture does not [ 41 ].…”
Section: Micrornasmentioning
confidence: 99%